Evaluation of the Use of Antidiabetic Drugs in Patients of Back-Referral Program at the Demak District Pharmacy - Nawang Wulan Nago Pitasari; Tri Murti Andayani; Tri Wijayanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Drugs are one of the important components of the Back-Referral Program (BRP), so the guarantee of the availability of BRP drugs in pharmacies is a factor in the success of BRP implementation. The purpose of this study was to determine the consumption of antidiabetic drugs using ATC/DDD and 90% DU methods, analyze the cost of consuming antidiabetic drugs, and determine the suitability of antidiabetic drugs with the National Formulary. This study was an observational study with a cross-sectional design and retrospective data collection. The study was conducted at 6 BRP pharmacies, namely Pharmacy A, Pharmacy B, Pharmacy C, Pharmacy D, Pharmacy E, and Pharmacy F in the area of Demak Regency. The antidiabetic drug consumption data was obtained from BRP patient prescriptions from July 2020 to June 2021. The cost data were obtained based on prices in the JKN drug e-catalog system at BRP pharmacies in the area of Demak Regency. In analyzing the data, the researcher calculated DU at 90%, the cost of drugs included in the DU segment at 90%, and the suitability of drugs with the National Formulary. The results showed that the highest consumption of antidiabetic drugs in Back-Referral Program (BRP) pharmacies in the area of Demak Regency was glimepiride (54.72%) and metformin (31.01%). The highest cost of consuming antidiabetic drugs per DDD was insulin (Rp.17,639.73), the lowest cost was glimepiride (Rp.65.35), the total cost of antidiabetic drugs was Rp.53,509,090 and an incompatible drug with National Formulary was pioglitazone. In general, the highest consumption of antidiabetic drugs in Back-Referral Program (BRP) 6th pharmacies in the area of Demak Regency, which was included in the DU segment 90%, were glimepiride, metformin and the suitability of drugs with the National Formulary has not reached 100%.